Three new combinations in African Cyperus (Cyperaceae) - Isabel Larridon (Plant Ecology and Evolution, 2019)
Background – During the past decade several molecular phylogenetic studies tackled the complex relationships within tribe Cypereae. Based on these studies, previously accepted segregate genera such as Pycreus were sunk into the genus Cyperus. Recently, while revising the West African species of Cyperus, three taxa previously placed in Pycreus were identified for which a name in Cyperus is lacking.Methods – The taxonomic changes are performed according to the International Code of Nomenclature for algae, fungi, and plants.Results – Three new combinations in Cyperus are made for names currently placed in Pycreus.